Persistent ascites after liver transplantation: etiology, treatment and impact on survival - Gotthardt, Daniel; Weiss, Karl Heinz; Rathenberg, Verena; Schemmer, Peter; Stremmel, Wolfgang; Sauer, Peter (Annals of transplantation, 2013)
[b]Background[/b] - Persistent ascites is an uncommon complication after orthotopic liver transplantation (OLT). Data on etiology, treatment and outcome are limited. - [b]Material and Methods[/b] - Data on 691 orthotopic liver transplantations in 585 patients were reviewed retrospectively. Patients with persistent ascites (longer than 4 weeks after successful liver transplantation) were selected and for each case two controls (no ascites after 4 weeks) were assigned and matched for age, sex, etiology of liver disease and pre-transplantation Child-Pugh-score/MELD-score. - [b]Results[/b] - Persistent ascites for more than 4 weeks after liver transplantation was present in 5.6% (33/585) patients and 4.8% (33/691) cases for a mean of 159±174 days. The most common underlying reason was bacterial or fungal peritonitis (69.7%; 23/33). Other etiologies included renal dysfunction (6%; 2/33), obstruction of the portal vein (3%; 1/33), and obstruction of the liver vein outflow (12%; 4/33); the etiology was unclear in 9% (3/33). - Liver function tests, c-reactive protein levels and parameters of renal function at 4 weeks post liver transplantation did not differ significantly between cases and controls. Patients with persistent ascites had refractory ascites before OLT significantly more often than controls. The 1-year survival rate was 92.3% for controls vs. 75.8% for cases (Kaplan Meier estimate p<0.05). - Treatment (paracentesis; diuretic medical treatment; antibiotic treatment for patients with peritonitis or bacterial infection; radiologic intervention in cases of underlying vascular obstruction) resolved ascites in 72.7% (24/33 patients). Ascites due to infection was treated successfully significantly more often than all other groups (p<0.05). - [b]Conclusions[/b] - Persistent ascites after liver transplantation is rare, but is associated with reduced 1-year survival. The underlying mechanisms are diverse, abdominal bacterial infection being the most common cause. The majority of cases can be successfully treated.
Gesehen am 19.02.2020